Learning to Sleep without Perching: Reflections by activist-educators on learning in social action in Ghanaian social movements - Langdon, Jonathan (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2009)
AbstractThis article conveys results from a participatory action research (PAR) engagement with activist/educators working in Ghanaian social movements. First, this PAR group has articulated two typologies from which to understand Ghanaian social movements based on their processes of organization, communication and learning rather than merely the issues, resources or populations that occupy their focus. Second, expanding on Griff Foley’s (1999) notion of learning in struggle, the PAR group provides three lenses from which to view learning in social movements in Ghana. Both of these contributions help to present a much needed African inflection to ongoing discussions of learning in social movements, especially as these contributions attempt to maintain a complex view of learning based on the shifting characteristics of power and capital.